2016
DOI: 10.1159/000445603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resveratrol on the Prevention of Intra-Abdominal Adhesion Formation in a Rat Model

Abstract: Background: Intra-abdominal adhesions are a very common complication following abdominal surgery. Our previous studies have demonstrated that the inhibition of inflammation at the sites of peritoneal injury can prevent the formation of intra-abdominal adhesions. Resveratrol is a natural extract with a broad range of anti-inflammatory effects. Therefore, we propose that resveratrol can reduce the formation of intra-abdominal adhesions after surgery. The aim of this study was to investigate the effect of resvera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 53 publications
2
27
0
8
Order By: Relevance
“…Resveratrol (RSV) is a stilbene polyphenolic compound found in grapes, berries, red wines, and peanut skins, and has been studied in many models such as coronary heart disease and diabetes due to its functions in reducing oxidative stress and inflammation [4-6]. In addition, many studies have shown that RSV can have protective effects on organs including the brain [7], heart [8], and kidney in animal IRI models because it reduces oxidative stress and exerts anti-inflammatory and anti-apoptotic effects [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol (RSV) is a stilbene polyphenolic compound found in grapes, berries, red wines, and peanut skins, and has been studied in many models such as coronary heart disease and diabetes due to its functions in reducing oxidative stress and inflammation [4-6]. In addition, many studies have shown that RSV can have protective effects on organs including the brain [7], heart [8], and kidney in animal IRI models because it reduces oxidative stress and exerts anti-inflammatory and anti-apoptotic effects [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…At present, the following pharmacological preventive strategies against postoperative intra-abdominal adhesions should be considered [15,16,17]: (1) minimizing the initial inflammatory reaction and exudate; (2) inhibiting agglutination of the exudate; (3) promoting fibrinolysis; (4) using a physical barrier that can isolate the injured surface coated with fibrin; and (5) inhibiting fibroblast proliferation. Unfortunately, most of the regimens that have been used to prevent adhesion formation have limited effectiveness and considerable side effects [18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that inhibiting the inflammatory reaction can prevent intra-abdominal adhesion in animals [26, 27]. Thus, it may be effective in preventing adhesion by inhibiting the inflammatory reaction and cytokines induction caused by injury.…”
Section: Discussionmentioning
confidence: 99%